2017
DOI: 10.1111/bpa.12585
|View full text |Cite
|
Sign up to set email alerts
|

CNS high‐grade neuroepithelial tumor with BCOR internal tandem duplication: a comparison with its counterparts in the kidney and soft tissue

Abstract: Central nervous system high-grade neuroepithelial tumors with BCOR alteration (CNS HGNET-BCOR) are a recently reported rare entity, identified as a small fraction of tumors previously institutionally diagnosed as so-called CNS primitive neuroectodermal tumors. Their genetic characteristic is a somatic internal tandem duplication in the 3' end of BCOR (BCOR ITD), which has also been found in clear cell sarcomas of the kidney (CCSK) and soft tissue undifferentiated round cell sarcomas/primitive myxoid mesenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 25 publications
7
93
2
Order By: Relevance
“…BCOR alterations have been recognized in a growing number of tumor subtypes affecting the soft tissue, the kidney or the central nervous system [22,38,39]. Recent studies comparing the molecular and histologic phenotype in these BCOR altered tumors found overlapping features, especially between soft tissue and kidney tumors [38,40,41]. At the level of DNA-methylation, we observed a great overlap in tumors from soft tissue and the kidney carrying BCOR alteration.…”
Section: Discussionmentioning
confidence: 52%
“…BCOR alterations have been recognized in a growing number of tumor subtypes affecting the soft tissue, the kidney or the central nervous system [22,38,39]. Recent studies comparing the molecular and histologic phenotype in these BCOR altered tumors found overlapping features, especially between soft tissue and kidney tumors [38,40,41]. At the level of DNA-methylation, we observed a great overlap in tumors from soft tissue and the kidney carrying BCOR alteration.…”
Section: Discussionmentioning
confidence: 52%
“…Only a few additional patients with HGNET BCOR ex15 ITD have been reported since the initial description of this tumor entity by Sturm et al . As such, the full spectrum of histologic features, accompanying genetic alterations, clinical outcomes, and optimal treatment for this new tumor entity remain largely undefined.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 ZC3H7B-BCOR and BCOR ITD define unique subsets of high-grade endometrial stromal sarcoma (ESS) mostly in adults. [16][17][18] BCOR ITD characterizes a subset of high-grade neuroepithelial tumors, mostly in children, [19][20][21] and EP300-BCOR defines a subset of pediatric glioma. 22 These various types of tumors show similar histology to the musculoskeletal counterpart, although each tumor type has distinct clinical features and/or a unique immunoprofile.…”
mentioning
confidence: 99%